Epistemologi: Dasar pengetahuan dalam filsafat ilmu - Orlando, Asadin Zidane (Maliki Interdisciplinary Journal, 2025)
Epistemology as a foundational branch of philosophy that examines the nature, sources, validity, and limitations of human knowledge. Epistemology provides a critical framework to evaluate how knowledge is acquired, justified, and distinguished from mere belief or misinformation. The discussion includes the historical development of epistemology and its main schools of thought—rationalism, empiricism, skepticism, criticism, positivism, and pragmatism—each offering distinct perspectives on the origin and reliability of knowledge. Furthermore, the paper highlights the essential role of epistemology in shaping scientific knowledge by establishing standards of truth, justification, and methodological rigor. A thorough understanding of epistemology empowers scholars and scientists to develop critical thinking and ethical responsibility in the pursuit and application of knowledge.